Kontribusi Perusahaan Pulp And Paper Serang bagi Kehidupan Masyarakat dan Pemerintah Daerah - Aryanti Puspokusumo (Binus Business Review, 2010)
The purpose of this study is to determine what contributions are provided by PT Indah Kiat Plup and Paper Tbk Serang Mill on the community and local government through the participation of Public Relation, especially in terms of education. The study is conducted from September 2009 until February 2010. The results showed that the community around the company has a large and direct impact on overall corporate performance. Community economic development in terms of education is a part of a Community Relation program conducted by the firm and has provided benefits to the community. Some suggestions for input to the company, includes optimizing the use of internal media organizations, granting broader authority for Public Relation so that they can better support the performance and needs of the company